Populism in Iceland: Has the Progressive Party turned populist? - Bergmann, Eiríkur (Stjórnsýslustofnun, 2015)
Though nationalism has always been strong in Iceland, populist political parties did not emerge as a viable force until after the financial crisis of 2008. On wave of the crisis a completely renewed leadership took over the country’s old agrarian party, the Progressive Party (PP), which was rapidly transformed in a more populist direction. Still the PP is perhaps more firmly nationalist than populist. However, when analyzing communicational changes of the new postcrisis leadership it is unavoidable to categorize the party amongst at least the softer version of European populist parties, perhaps closest to the Norwegian Progress Party.